The Influence of Brand Image, Brand Experience, and Brand Satisfaction on Brand Loyalty in Avoskin Skincare (A Study of Avoskin Skincare Consumers in Surabaya) - Andramaya Kusuma Ningtyas; R. Yuniardi Rusdianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
Technological advancements and global market developments have driven of the beauty sector in Indonesia. Positive prospects in the beauty sector encourage many local brands, including Avoskin to compete in an increasingly competitive market. In this competition, the brand's ability to build and maintain Brand Loyalty is the key to success. The purpose of the research conducted is to analyze the influence of Brand Image, Brand Experience, and Brand Satisfaction on Brand Loyalty in Avoskin skincare (A Study of Avoskin Skincare Consumers in Surabaya City). This study adopted a quantitative method with an associative descriptive type. The data collection technique in this study was an online questionnaire via Google Form. The study sample consisted of 150 respondents who live in the city of Surabaya and have purchased Avoskin skincare products. The statistical analysis employed in this study is multiple linear regression. The findings of the study show that Brand Image, Brand Experience, and Brand Satisfaction simultaneously have a significant influence on Avoskin skincare Brand Loyalty. Partially, Brand Image exhibits a significant positive influence on Avoskin skincare Brand Loyalty, Brand Experience exhibits a significant positive influence on Avoskin skincare Brand Loyalty, and Brand Satisfaction exhibits a significant positive influence on Avoskin skincare Brand Loyalty.